1994
DOI: 10.1136/jcp.47.12.1098
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta 1 as a prognostic factor in pulmonary adenocarcinoma.

Abstract: Aims-To evaluate the efficacy of transforming growth factor f/ (TGF-/I) for the prognosis of pulmonary adenocarcinoma. Methods-TGF-/J was detected immunohistochemically using the avidin-biotinperoxidase complex technique in resected pulmonary adenocarcinomas from 88 patients. Results-Of the 88 patients, 39 were TGF-/I negative and 45 TGF-fl positive.The five year survival rate was 56% for the TGF-fl negative and 16% for the TGF-fl positive group. Conclusions-TGF-/i can be used as a prognostic factor in pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 11 publications
1
17
0
2
Order By: Relevance
“…This result is in consistent with the previous studies (Takanami et al, 1994;Takanami et al, 1997). Although the specific mechanism is still not very clear, the high expression of TGF-β1 protein in NSCLC tissues may be related to reduction of TβR (TGF-β receptor) and abnormity of Smads protein.…”
Section: Discussionsupporting
confidence: 82%
“…This result is in consistent with the previous studies (Takanami et al, 1994;Takanami et al, 1997). Although the specific mechanism is still not very clear, the high expression of TGF-β1 protein in NSCLC tissues may be related to reduction of TβR (TGF-β receptor) and abnormity of Smads protein.…”
Section: Discussionsupporting
confidence: 82%
“…Numerous studies showed that the loss or reduction of the E-cadherin-β-catenin complex is associated with metastasis and a poor prognosis in non-small cell carcinomas of the lung (5,6,26,27). Moreover, the TGF-β expression was reported to be associated with poor prognosis of patients with adenocarcinomas of the lung (18,19). Therefore, the reduced expression of E-cadherin and β-catenin and the increased expression of TGF-β in PCs appear to be associated with the aggressiveness of PCs.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor (TGF)-β is one of the epithelial-mesencymal transition-inducing factors (14,16,17). TGF-β has been reported to be associated with poor prognosis of patients with certain types of cancer including lung cancer (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported in other types of solid tumours. Takanami and colleagues (1994) have demonstrated that TGF-I1 was an independent prognostic indicator in patients with pulmonary adenocarcinoma (Takanami et al 1994). Gorsch and colleagues (1992) described an association between the intensity of TGF-31 immunoreactisity in breast carcinoma specimens and disease-free survival that was independent of established prognostic variables (Gorsch et al 1992).…”
Section: Methodsmentioning
confidence: 99%